On the way to NFT: About the ‘practical limits’ of Copyright in peruvian law in the case of digital pictoric art - Arcasi Sosa, Daniella Elizabeth (2022)
The Peruvian Copyright protection regime is attached to a closed system of limitations and exceptions. However, this rigor presents “practical limits” in its application, which do not allow the realization of the purpose of this institution. It will be analyzed how these “practical limits” are presented in the dynamics through the Internet in the case of digital pictorial works. Likewise, we will demonstrate how the rise of transactions through “non-fungible tokens” (NFT) have represented an alternative route to traditional marketing for artist authors in the face of the high diffusion and reproduction of their works on the network. These NFT transactions will demonstrate the ineffectiveness of the traditional protection and incentive of the legal system towards creative, intellectual, and artistic freedom.